# How do you solve #(x+1)/3 = (2x-1)/4#?

##### 2 Answers

Jun 21, 2018

#### Explanation:

#"multiply both sides by the lowest common multiple of"#

#"3 and 4 that is 12"#

#cancel(12)^4xx(x+1)/cancel(3)^1=cancel(12)^3xx(2x-1)/cancel(4)^1#

#4(x+1)=3(2x-1)larrcolor(blue)"distribute"#

#4x+4=6x-3#

#"subtract "4x" from both sides"#

#4=2x-3#

#"add 3 to both sides and divide by 2"#

#7=2xrArrx=7/2#

#color(blue)"As a check"#

#"left "=(7/2+2/2)/3=(9/2)/3=9/6=3/2#

#"right "=(14/2-2/2)/4=6/4=3/2#

#x=7/2" is the solution"#

Jun 21, 2018

#### Explanation:

Multiply both sides by

So, the equation becomes

Expand both sides to get

Subtract

Subtract

Divide both sides by